2022
DOI: 10.3389/fphys.2022.881484
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Six-Week Prehabilitation With Blood-Flow Restriction Training on Pre- and Postoperative Skeletal Muscle Mass and Strength in Patients Receiving Primary Total Knee Arthroplasty

Abstract: Introduction: Total Knee Arthroplasty (TKA) is one of the most successful interventions in gonarthrosis, however the operation is leading to muscle atrophy and long-term muscular deficits. To enhance rehabilitation after TKA, exercise programs try to improve muscle function preoperatively, called prehabilitation. Blood-Flow-Restriction Exercises (BFRE) is a training method which is characterized by using tourniquets to reduce arterial and occlude venous blood flow simultaneously during the exercise to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 41 publications
1
23
1
Order By: Relevance
“…One major factor that could contribute to low adherence could be increased pain while performing the exercises. Forty-one trials (85%) [52][53][54][55][56][57][58][59][60][61][62][63][64][66][67][68][69][70][71][72][75][76][77]79,80,82,[84][85][86][87][88][89][90][91][92][93][94][95][96]98,99 in this review included patients with degenerative joint diseases awaiting joint replacement surgery. Exercises loading the joints can induce further discomfort and could result in low adherence to the exercise program that can affect treatment outcomes, particularly in older people with long-term conditions such as osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One major factor that could contribute to low adherence could be increased pain while performing the exercises. Forty-one trials (85%) [52][53][54][55][56][57][58][59][60][61][62][63][64][66][67][68][69][70][71][72][75][76][77]79,80,82,[84][85][86][87][88][89][90][91][92][93][94][95][96]98,99 in this review included patients with degenerative joint diseases awaiting joint replacement surgery. Exercises loading the joints can induce further discomfort and could result in low adherence to the exercise program that can affect treatment outcomes, particularly in older people with long-term conditions such as osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-seven trials (77%) 52,[55][56][57][58][60][61][62][63][64][65][66][67][68][71][72][73][74][75][76][77][78][79][82][83][84][86][87][88][89][91][92][93][94][95][96][97][98][99] included in this review delivered prehabilitation twice a week over at least 4 weeks. This finding is in accordance with a recent umbrella review of 55 systematic reviews on prehabilitation for patients undergoing major surgical procedures 118 and physiological literature to indicate 4 to 6 weeks of strength training is required to induce neurological and morphological muscular adaptations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies have demonstrated the bene t of BFR for the population with disease impairment, especially the signi cant effect of AE-BFR on increasing aerobic capacity. There were patients with post-infarction heart failure, chronic kidney disease on hemodialysis, or end-stage gonarthrosis participated underwent either AE or AE-BFR, and the results showed that AE-BFR achieved greater aerobic capacity improvement than AE [54,91,92]. Patients with multiple sclerosis (MS) and severe gait disabilities showed improvement in aerobic capacity after AE-BFR, but no difference with AE [93].…”
Section: Aerobic Capacitymentioning
confidence: 99%